Different patterns of A*80:01:01:01 allele generation based on exon or intron sequences. Issue 1 (17th December 2014) - Cervera, I.; Herraiz, M. A; Vidart, J.; Ortega, S.; Martínez‐Laso, J.
Abstract Generation of the HLA‐A*80:01:01:01 allele has been analysed using its complete sequence. Direct comparison of the sequences and phylogenetic trees using the human leukocyte antigen (HLA)‐A representative alleles and the major histocompatibility complex (MHC)‐A sequences of non‐human primates has been made. Results based on exon sequences confirm previously published, but considering only the sequences of the introns, two distinct regions can be differentiated. The first one comprises from the 5′ untranslated region region to the first part of intron 3 sequence (shared with A2 family), and the second one includes the sequence from the end of intron 3 to intron 7 (shared with A1/A3/A11/A36/A30 family). Each of them clusters with Gorilla and Chimpanzee MHC‐A sequences, respectively, suggesting an origin coming from a common ancestor to Gorilla and Chimpanzee.